(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
Educational buildings have a strategic role in supporting educational progress by providing facilities and a conducive learning environment. In order to meet these needs, an Education and Creativity Center Building Structure was designed in Semarang City. Technically, the building structure planning considers the geologic condition of Semarang City which is prone to earthquakes. Therefore, structural analysis was conducted using SAP2000 software to ensure the safety and stability of the building. The main structure uses reinforced concrete (f’c = 30 MPa) and reinforcing steel (fy = 420 MPa), with structural components such as K1 (80 x 80 cm) and K2 (45 x 45 cm) columns, B1 (35 x 70 cm) and B2 (25 x 50 cm) type beams, 13 cm thick floor slabs, and a steel roof structure truss system for construction efficiency. For the foundation system, 15-meter-long spun pile with a diameter of 50 cm are used, which are connected to pile cap types PC1, PC2 and PC3 as load spreading elements. Tie beams measuring 30×60 cm are used to structurally tie the foundation. All structural elements were designed with strength, material efficiency, and sustainability in mind, so that the building is expected to become an educational and creative center that can support community growth and improve the quality of education in Semarang.